KEPENTINGAN KOLOMBIA MEMPERTAHANKAN KEPULAUAN SAN ANDREAS DARI KLAIM NIKARAGUA PASCA KEPUTUSAN MAHKAMAH INTERNASIONAL TAHUN 2012 - Sari, Dewi Ratna; Harto, Syafri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research will discuss the interest of maintaining Colombia's the Island of San Andres Nicaragua claim after an international court of Justice decision in 2012. Dispute Nicaraguan territory won by getting the right area of 200 nautical miles as the state beach. To maintain the islands of San Andreas Colombia rejected the international court's decision.Perspective used in this research is Neorealist. This research uses the theory of conflict by K.J Holsti. Based on this theory conflicts caused conflict in achieving a particular goal, such as territorial defense, security, natural resources in order to maintain or achieve a particular goal. Conflicts also include diplomatic actions and propaganda struggle and threats.Colombia has economic and political interests in the islands of San Andreas. From the political aspect of these islands is the border region that is leading the island state security. Islands San Andreas also has potential in the field of marine economy, and tourism. To the national interest, Colombia rejects international court decisionsKeyword : Dispute, Neorealist, territorial defense, tourism.